PENGKLASIFIKASIAN KEMAMPUAN AKADEMIK MAHASISWA MENGGUNAKAN ANALISIS CLUSTER BERDASARKAN NILAI MATA KULIAH SAINS DASAR - Mahfuz Hudori (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The Cumulative Grade Point Average (CGPA) of heterogeneous students can serve as an indication of differences in academic abilities among them. This condition needs to be minimized to ensure that students' competencies are distributed evenly and maximized. Grouping is an effort that can be undertaken to address the heterogeneity of student's academic abilities. This research aims to classify the academic potential of Civil Engineering students at the Universitas International Batam based on the scores of basic science courses using cluster analysis. The cluster analysis in this research utilizes the Ward method and Euclidean distance to measure the distance between objects. The results of the classification show that the Civil Engineering students at Universitas International Batam 2019 can be divided into three clusters. The first cluster consists of 9 students with the best academic abilities. The second cluster consists of 9 students with fairly good academic abilities. The third cluster consists of 11 students with inadequate academic abilities